A method for preparing a high-niobium porous layered titanium-aluminum alloy plate

By preparing high niobium porous layered titanium-aluminum alloy plates, the existing layered titanium-aluminum composite plates have been solved, and the excellent mechanical properties and high and low temperature resistance of the sheets have been achieved.

CN118773463BActive Publication Date: 2025-04-25SHANDONG ZHONGXIN INNOVATION MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410725470.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-04-25
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

The existing layered titanium-aluminum composite panels have problems such as high cost, high technical difficulty, insufficient bonding strength and poor low temperature resistance in the application of existing layered titanium-aluminum composite panels in the aerospace field.

Method used

By using niobium powder, titanium powder and graphite powder as raw materials, niobium titanium carbon composite powder, mixed with aluminum powder, then preparing niobium titanium aluminum alloy, and rolling at multiple times at high temperatures to form niobium titanium aluminum composite foil. Then, the niobium-titanium-aluminum composite foil was alternately stacked with the mixed powder, and was subjected to room temperature cold rolling, hot diffusion composite and laser remelting to prepare a high niobium porous layered titanium-aluminum alloy plate.

Benefits of technology

It achieves excellent mechanical properties and high and low temperature resistance of the plate, and improves the application prospects of aerospace materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004878478290000091
    Figure BDA0004878478290000091
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-niobium porous layered titanium-aluminum alloy plate, firstly using niobium powder, titanium powder and graphite powder as raw materials to prepare niobium-titanium-carbon composite powder, then mixing the niobium-titanium-carbon composite powder with aluminum powder to obtain mixed powder; then using niobium powder, titanium dihydride powder and aluminum powder as raw materials to prepare niobium-titanium-aluminum alloy, and performing multiple high-temperature rolling to obtain niobium-titanium-aluminum composite foil; finally, the niobium-titanium-aluminum composite foil and the mixed powder are alternately stacked, cold rolled at room temperature, thermally diffused and composited, and laser remelted to obtain the plate. The plate has excellent mechanical properties and high and low temperature resistance, and has very good application prospects in aerospace material processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing an alloy plate, and in particular to a method for preparing a high-niobium porous layered titanium-aluminum alloy plate, belonging to the technical field of metal material processing. Background Art

[0002] In the field of aerospace, aircraft and their power units, instruments, etc. require a variety of materials. Due to the special working environment of aerospace materials, they often require excellent high and low temperature resistance, aging resistance and corrosion resistance. However, industrial materials prepared by traditional processes, especially single metal materials, are far from the high standards required for aerospace materials. Therefore, the preparation of composite materials is a hot topic in the current research of aerospace materials.

[0003] Titanium-aluminum-based materials have properties such as high temperature resistance and oxidation resistance, and are one of the best materials for high-temperature components in the aerospace field. At present, layered titanium-aluminum composite plates have been used in the aerospace field. Layered titanium-aluminum composite plates are composite materials composed of titanium and aluminum, which have both the thermal conductivity of aluminum and the high temperature resistance of titanium. The preparation methods of layered titanium-aluminum composite plates mainly include explosive compounding, rolling compounding, thermal diffusion compounding, etc. Among them, explosive compounding is the most important production method of layered titanium-aluminum composite plates. However, the cost of explosive compounding is high and the technical difficulty is relatively large. The huge instantaneous energy generated by the explosion of the charge is used to achieve the metallurgical bonding between the titanium plate and the aluminum plate. The deformation of the plate during the explosion is difficult to control, and the titanium-aluminum interface is more likely to produce defects and impurities, which reduces the yield rate of the product. The layered composite plates prepared by rolling compounding and thermal diffusion compounding have insufficient bonding strength between the layers, which affects the product performance and service life.

[0004] Patent CN110170527B discloses a method for preparing a high-niobium porous layered titanium-aluminum alloy sheet, which is carried out according to the following steps:

[0005] Step 1: mixing aluminum powder and niobium powder evenly by ball milling, and then hot pressing and sintering in vacuum to obtain an aluminum-niobium alloy material;

[0006] Step 2: performing multiple high-temperature rolling on the aluminum-niobium alloy material until it becomes a foil sheet to obtain an aluminum-niobium composite foil;

[0007] Step 3, pre-treating the surfaces of the titanium foil and the aluminum-niobium composite foil respectively;

[0008] Step 4: alternately stacking the titanium foil and the aluminum-niobium composite foil processed in step 3 in a graphite mold with the inner wall sprayed with boron nitride;

[0009] Step 5: Then perform pressurization and heat treatment to obtain a high-niobium porous layered titanium-aluminum alloy sheet.

[0010] This patented technology introduces niobium and aluminum alloying to prepare aluminum-niobium composite foil, which is then alternately stacked with titanium foil and subjected to pressurized heat treatment to form a layered plate. The bonding strength between the layers is average, which seriously affects the service life of the product. In addition, the top and bottom layers of the plate are titanium foil, and the product performance is average, especially the low-temperature resistance is poor. Summary of the invention

[0011] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a method for preparing a high-niobium porous layered titanium-aluminum alloy plate, wherein the obtained plate has excellent mechanical properties and high and low temperature resistance.

[0012] To achieve the above object, the present invention adopts the following technical solutions:

[0013] A method for preparing a high-niobium porous layered titanium-aluminum alloy plate, the specific steps are as follows:

[0014] (1) firstly prepare niobium titanium carbon composite powder using niobium powder, titanium powder and graphite powder as raw materials, and then mix the niobium titanium carbon composite powder with aluminum powder to obtain mixed powder;

[0015] (2) Then, niobium powder, titanium dihydride powder and aluminum powder are used as raw materials to prepare niobium titanium aluminum alloy, and high-temperature rolling is performed for multiple passes to obtain niobium titanium aluminum composite foil;

[0016] (3) Finally, the niobium-titanium-aluminum composite foil and the mixed powder are alternately stacked, cold-rolled at room temperature, thermally diffused and composited, and laser remelted to obtain the high-niobium porous layered titanium-aluminum alloy plate.

[0017] Preferably, in step (1), the molar ratio of niobium powder, titanium powder and graphite powder is 1:1.2-1.5:1.5-1.7; and the particle size of niobium powder, titanium powder and graphite powder is 300-400 mesh.

[0018] Preferably, in step (1), the niobium-titanium-carbon composite powder is prepared by the following method: firstly, niobium powder and titanium powder are mixed by preliminary ball milling to obtain a niobium-titanium premix, and then the niobium-titanium premix is ​​further mixed by ball milling with graphite powder to obtain the niobium-titanium-carbon composite powder; the ball milling operation is carried out under an argon atmosphere.

[0019] Further preferably, the process conditions for preliminary ball milling and mixing are: ball milling at 300-500 r / min for 1-2 hours; the process conditions for further ball milling and mixing are: ball milling at 300-500 r / min for 2-3 hours; the ball milling uses 10 mm diameter zirconia grinding balls, and the ball-to-material ratio during ball milling (the mass ratio of grinding balls to ball-milled materials) is 30-35:1.

[0020] Preferably, in step (1), the mass ratio of niobium-titanium-carbon composite powder to aluminum powder is 7 to 9:100.

[0021] Preferably, in step (2), the niobium-titanium-aluminum alloy is prepared by the following method: first, niobium powder, titanium dihydride powder and aluminum powder are ball-milled and mixed in a mass ratio of 1:1.5 to 2:6 to 7, pressed into a green body, sintered, and cooled to room temperature in a furnace; the particle size of niobium powder, titanium dihydride powder and aluminum powder is 300 to 400 mesh.

[0022] Further preferably, the process conditions for ball milling are: ball milling at 300-500 r / min for 4-5 hours; using 10 mm diameter zirconia grinding balls, and the ball-to-material ratio (mass ratio of grinding balls to ball-milled materials) during ball milling is 25-30:1.

[0023] More preferably, the pressing is performed under a pressure of 1 to 2 GPa.

[0024] Further preferably, the sintering process conditions are: first heat to 500-550°C at 10-15°C / min, keep warm for 30-40 minutes, then heat to 900-950°C at 8-10°C / min, keep warm for 30-40 minutes, then heat to 1000-1100°C at 20-30°C / min, keep warm for 30-40 minutes, finally heat to 1200-1300°C at 5-7°C / min, pass argon to 25-30MPa, and keep warm and pressure for 2-3 hours; sintering is carried out in argon atmosphere.

[0025] Preferably, in step (2), the specific method of multiple high-temperature rolling is as follows: first, the niobium-titanium-aluminum alloy is heated to 450-550°C, kept warm for 20-30 minutes, and then high-temperature rolling is performed under this temperature condition to finally obtain a niobium-titanium-aluminum composite foil with a thickness of 1 mm.

[0026] Preferably, in step (3), each layer of the mixed powder and the niobium-titanium-aluminum composite foil have the same thickness, and the layers are alternately stacked for a total of 2n+1 layers, wherein the mixed powder is n layers, the niobium-titanium-aluminum composite foil is n+1 layers, the top and bottom layers are niobium-titanium-aluminum composite foils, and n is a positive integer. n is more preferably 5.

[0027] Preferably, in step (3), after alternate lamination, the powder is wrapped with titanium foil and cold rolled at room temperature with a deformation of 25-30%, so as to promote a more uniform distribution of the mixed powder.

[0028] Preferably, in step (3), the graphite is placed in a graphite mold uniformly sprayed with boron nitride and thermally diffused in a vacuum sintering furnace. The specific process conditions are as follows: first, -2 MPa vacuum condition, heat up to 200-300℃ at 5-8℃ / min, keep warm for 50-60 minutes, then heat up to 550-650℃ at 8-10℃ / min, pressurize to 70-80MPa, keep warm for 7-8 hours, remove pressure, keep warm for 1-2 hours, cool to room temperature with the furnace; then heat at 10-2 MPa vacuum condition, heat up to 1000-1100℃ at 15-20℃ / min, keep warm for 30-40 minutes, then heat up to 1200-1250℃ at 4-6℃ / min, pressurize to 40-50MPa, keep warm for 2-3 hours, remove the pressure, keep warm for 1-2 hours, cool to room temperature with the furnace, and remove the jacket.

[0029] Preferably, in step (3), the process conditions of laser remelting are: laser spot diameter is 2 to 3 mm, laser power is 2 to 3 kW, and scanning speed is 130 to 140 mm / min.

[0030] A high-niobium porous layered titanium-aluminum alloy plate is obtained by the above-mentioned preparation method.

[0031] The aforementioned high niobium porous layered titanium aluminum alloy plate is used in aerospace material processing.

[0032] Beneficial effects of the present invention:

[0033] The present invention first uses niobium powder, titanium powder and graphite powder as raw materials to prepare niobium titanium carbon composite powder, then mixes the niobium titanium carbon composite powder with aluminum powder to obtain mixed powder; then uses niobium powder, titanium dihydride powder and aluminum powder as raw materials to prepare niobium titanium aluminum alloy, and performs multiple high-temperature rolling to obtain niobium titanium aluminum composite foil; finally, the niobium titanium aluminum composite foil and the mixed powder are alternately stacked, cold rolled at room temperature, thermally diffused and composited, and laser remelted to obtain a high-niobium porous layered titanium aluminum alloy plate. The plate has excellent mechanical properties and high and low temperature resistance, and has very good application prospects in aerospace material processing.

[0034] The present invention forms a porous layered structure by alternately laminating niobium-titanium-aluminum composite foil and mixed powder, cold rolling at room temperature, and thermal diffusion compounding. The layers have strong bonding strength, and the subsequent surface laser remelting treatment synergistically improves the performance of the plate.

[0035] The bonding force between the layers is derived from the selection of the materials of each layer and the adjustment of the specific process parameters of the composite process. The mixed powder of the present invention is obtained by mixing niobium titanium carbon composite powder prepared from niobium powder, titanium powder and graphite powder with aluminum powder. During the thermal diffusion composite process, the niobium titanium carbon composite powder produces a large number of defects such as vacancies and dislocations, which promotes the refinement of the structure. The mixed powder is fully diffused into the niobium titanium aluminum composite foil, and the layers are fully composited into one.

[0036] The applicant screened the specific process parameters of the composite process and optimized the microstructure by adjusting the heating rate, temperature, pressure, etc., thereby improving the performance of the sheet. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with embodiments. It should be noted that the following description is only for explaining the present invention and does not limit its contents.

[0038] Embodiment 1:

[0039] A method for preparing a high-niobium porous layered titanium-aluminum alloy plate, the specific steps are as follows:

[0040] (1) firstly prepare niobium titanium carbon composite powder using niobium powder, titanium powder and graphite powder as raw materials, and then mix the niobium titanium carbon composite powder with aluminum powder in a mass ratio of 7:100 to obtain a mixed powder;

[0041] (2) Then, niobium powder, titanium dihydride powder and aluminum powder are used as raw materials to prepare niobium titanium aluminum alloy, and high-temperature rolling is performed for multiple passes to obtain niobium titanium aluminum composite foil;

[0042] (3) Finally, the niobium-titanium-aluminum composite foil and the mixed powder are alternately stacked, cold-rolled at room temperature, thermally diffused and composited, and laser remelted to obtain the high-niobium porous layered titanium-aluminum alloy plate.

[0043] Wherein, in step (1), the molar ratio of niobium powder, titanium powder and graphite powder is 1:1.2:1.5; and the particle size of niobium powder, titanium powder and graphite powder is 300 mesh.

[0044] The niobium-titanium-carbon composite powder is prepared by the following method: niobium powder and titanium powder are firstly ball-milled to obtain a niobium-titanium premix, and the niobium-titanium premix is ​​further ball-milled with graphite powder to obtain the niobium-titanium-carbon composite powder; the ball milling operation is performed under an argon atmosphere.

[0045] The process conditions for preliminary ball milling and mixing are: ball milling at 300 r / min for 1 hour; the process conditions for further ball milling and mixing are: ball milling at 300 r / min for 2 hours; the ball milling uses 10 mm diameter zirconia grinding balls, and the ball-to-material ratio (mass ratio of grinding balls to ball-milled materials) during ball milling is 30:1.

[0046] In step (2), the niobium-titanium-aluminum alloy is prepared by the following method: first, niobium powder, titanium dihydride powder and aluminum powder are ball-milled and mixed in a mass ratio of 1:1.5:6, pressed into a green body under a pressure of 1 GPa, sintered, and cooled to room temperature in a furnace; the particle size of niobium powder, titanium dihydride powder and aluminum powder is 300 mesh.

[0047] The process conditions of ball milling are: ball milling at 300 r / min for 4 hours; zirconia grinding balls with a diameter of 10 mm are used for ball milling, and the ball-to-material ratio (mass ratio of grinding balls to ball-milled materials) during ball milling is 25:1.

[0048] The sintering process conditions are as follows: first increase the temperature to 500°C at 10°C / min, keep warm for 30 minutes, then increase the temperature to 900°C at 8°C / min, keep warm for 30 minutes, then increase the temperature to 1000°C at 20°C / min, keep warm for 30 minutes, and finally increase the temperature to 1200°C at 5°C / min, pass argon to 25MPa, and keep warm and pressure for 2 hours; sintering is carried out in argon atmosphere.

[0049] The specific method of multi-pass high-temperature rolling is as follows: firstly, the niobium-titanium-aluminum alloy is heated to 450°C, kept at this temperature for 20 minutes, and then high-temperature rolled under this temperature condition to finally obtain a niobium-titanium-aluminum composite foil with a thickness of 1 mm.

[0050] In step (3), each layer of mixed powder and niobium titanium aluminum composite foil has the same thickness, and a total of 11 layers are alternately stacked, including 5 layers of mixed powder and 6 layers of niobium titanium aluminum composite foil, with the top and bottom layers being niobium titanium aluminum composite foil.

[0051] After alternate lamination, the mixed powder is wrapped with titanium foil and cold rolled at room temperature with a deformation of 25%, which promotes a more uniform distribution of the mixed powder.

[0052] Place it in a graphite mold uniformly sprayed with boron nitride and perform thermal diffusion composite in a vacuum sintering furnace. The specific process conditions are as follows: first, -2 MPa vacuum condition, the temperature was raised to 200°C at 5°C / min, kept at that temperature for 50 minutes, then raised to 550°C at 8°C / min, pressurized to 70MPa, kept at that temperature for 7 hours, the pressure was removed, kept at that temperature for 1 hour, and cooled to room temperature with the furnace; then -2 MPa vacuum condition, heat to 1000℃ at 15℃ / min, keep warm for 30 minutes, then heat to 1200℃ at 4℃ / min, pressurize to 40MPa, keep warm for 2 hours, remove the pressure, keep warm for 1 hour, cool to room temperature with the furnace, and remove the cover.

[0053] The process conditions of laser remelting are: laser spot diameter of 2 mm, laser power of 2 kW, and scanning speed of 130 mm / min.

[0054] Embodiment 2:

[0055] A method for preparing a high-niobium porous layered titanium-aluminum alloy plate, the specific steps are as follows:

[0056] (1) firstly prepare niobium titanium carbon composite powder using niobium powder, titanium powder and graphite powder as raw materials, and then mix the niobium titanium carbon composite powder with aluminum powder in a mass ratio of 9:100 to obtain a mixed powder;

[0057] (2) Then, niobium powder, titanium dihydride powder and aluminum powder are used as raw materials to prepare niobium titanium aluminum alloy, and high-temperature rolling is performed for multiple passes to obtain niobium titanium aluminum composite foil;

[0058] (3) Finally, the niobium-titanium-aluminum composite foil and the mixed powder are alternately stacked, cold-rolled at room temperature, thermally diffused and composited, and laser remelted to obtain the high-niobium porous layered titanium-aluminum alloy plate.

[0059] Wherein, in step (1), the molar ratio of niobium powder, titanium powder and graphite powder is 1:1.5:1.7; and the particle size of niobium powder, titanium powder and graphite powder is 400 mesh.

[0060] The niobium-titanium-carbon composite powder is prepared by the following method: niobium powder and titanium powder are firstly ball-milled to obtain a niobium-titanium premix, and the niobium-titanium premix is ​​further ball-milled with graphite powder to obtain the niobium-titanium-carbon composite powder; the ball milling operation is performed under an argon atmosphere.

[0061] The process conditions for preliminary ball milling and mixing are: ball milling at 500 r / min for 2 hours; the process conditions for further ball milling and mixing are: ball milling at 500 r / min for 3 hours; the ball milling uses 10 mm diameter zirconia grinding balls, and the ball-to-material ratio (mass ratio of grinding balls to ball-milled materials) during ball milling is 35:1.

[0062] In step (2), the niobium-titanium-aluminum alloy is prepared by the following method: first, niobium powder, titanium dihydride powder and aluminum powder are ball-milled in a mass ratio of 1:2:7, pressed into a green body under a pressure of 2 GPa, sintered, and cooled to room temperature in a furnace; the particle size of niobium powder, titanium dihydride powder and aluminum powder is 400 mesh.

[0063] The process conditions of ball milling are: 500r / min ball milling for 5 hours; 10mm diameter zirconia grinding balls are used for ball milling, and the ball-to-material ratio (mass ratio of grinding balls to ball-milled materials) during ball milling is 30:1.

[0064] The sintering process conditions are as follows: first increase the temperature to 550°C at 15°C / min, keep warm for 40 minutes, then increase the temperature to 950°C at 10°C / min, keep warm for 40 minutes, then increase the temperature to 1100°C at 30°C / min, keep warm for 40 minutes, and finally increase the temperature to 1300°C at 7°C / min, pass argon to 30MPa, and keep warm and pressure for 3 hours; sintering is carried out in argon atmosphere.

[0065] The specific method of multi-pass high-temperature rolling is as follows: firstly, the niobium-titanium-aluminum alloy is heated to 550°C, kept at this temperature for 30 minutes, and then high-temperature rolled under this temperature condition to finally obtain a niobium-titanium-aluminum composite foil with a thickness of 1 mm.

[0066] In step (3), each layer of mixed powder and niobium titanium aluminum composite foil has the same thickness, and a total of 11 layers are alternately stacked, including 5 layers of mixed powder and 6 layers of niobium titanium aluminum composite foil, with the top and bottom layers being niobium titanium aluminum composite foil.

[0067] After alternate lamination, the mixed powder is wrapped with titanium foil and cold rolled at room temperature with a deformation of 30%, which promotes a more uniform distribution of the mixed powder.

[0068] Place it in a graphite mold uniformly sprayed with boron nitride and perform thermal diffusion composite in a vacuum sintering furnace. The specific process conditions are as follows: first, -2 MPa vacuum condition, the temperature was raised to 300℃ at 8℃ / min, kept at that temperature for 60 minutes, then raised to 650℃ at 10℃ / min, pressurized to 80MPa, kept at that temperature for 8 hours, the pressure was removed, kept at that temperature for 2 hours, and cooled to room temperature with the furnace; then at 10 -2 MPa vacuum condition, heat to 1100℃ at 20℃ / min, keep warm for 40 minutes, then heat to 1250℃ at 6℃ / min, pressurize to 50MPa, keep warm for 3 hours, remove the pressure, keep warm for 2 hours, cool to room temperature with the furnace, and remove the cover.

[0069] The process conditions of laser remelting are: laser spot diameter of 3 mm, laser power of 3 kW, and scanning speed of 140 mm / min.

[0070] Embodiment 3:

[0071] A method for preparing a high-niobium porous layered titanium-aluminum alloy plate, the specific steps are as follows:

[0072] (1) firstly prepare niobium titanium carbon composite powder using niobium powder, titanium powder and graphite powder as raw materials, and then mix the niobium titanium carbon composite powder with aluminum powder in a mass ratio of 8:100 to obtain a mixed powder;

[0073] (2) Then, niobium powder, titanium dihydride powder and aluminum powder are used as raw materials to prepare niobium titanium aluminum alloy, and high-temperature rolling is performed for multiple passes to obtain niobium titanium aluminum composite foil;

[0074] (3) Finally, the niobium-titanium-aluminum composite foil and the mixed powder are alternately stacked, cold-rolled at room temperature, thermally diffused and composited, and laser remelted to obtain the high-niobium porous layered titanium-aluminum alloy plate.

[0075] Wherein, in step (1), the molar ratio of niobium powder, titanium powder and graphite powder is 1:1.3:1.6; and the particle size of niobium powder, titanium powder and graphite powder is 400 mesh.

[0076] The niobium-titanium-carbon composite powder is prepared by the following method: niobium powder and titanium powder are firstly ball-milled to obtain a niobium-titanium premix, and the niobium-titanium premix is ​​further ball-milled with graphite powder to obtain the niobium-titanium-carbon composite powder; the ball milling operation is performed under an argon atmosphere.

[0077] The process conditions for preliminary ball milling and mixing are: ball milling at 400 r / min for 1.5 hours; the process conditions for further ball milling and mixing are: ball milling at 400 r / min for 3 hours; the ball milling uses 10 mm diameter zirconia grinding balls, and the ball-to-material ratio (mass ratio of grinding balls to ball-milled materials) during ball milling is 32:1.

[0078] In step (2), the niobium-titanium-aluminum alloy is prepared by the following method: first, niobium powder, titanium dihydride powder and aluminum powder are ball-milled and mixed in a mass ratio of 1:1.8:6.5, pressed into a green body under a pressure of 2 GPa, sintered, and cooled to room temperature in a furnace; the particle size of niobium powder, titanium dihydride powder and aluminum powder is 400 mesh.

[0079] The process conditions of ball milling are: 400r / min ball milling for 4.5 hours; 10mm diameter zirconia grinding balls are used for ball milling, and the ball-to-material ratio (mass ratio of grinding balls to ball-milled materials) during ball milling is 28:1.

[0080] The sintering process conditions are as follows: first increase the temperature to 530°C at 12°C / min, keep warm for 35 minutes, then increase the temperature to 920°C at 9°C / min, keep warm for 35 minutes, then increase the temperature to 1050°C at 25°C / min, keep warm for 35 minutes, and finally increase the temperature to 1250°C at 6°C / min, pass argon to 30MPa, and keep warm and pressure for 2 hours; sintering is carried out in argon atmosphere.

[0081] The specific method of multi-pass high-temperature rolling is as follows: firstly, the niobium-titanium-aluminum alloy is heated to 500°C, kept at this temperature for 25 minutes, and then high-temperature rolled under this temperature condition to finally obtain a niobium-titanium-aluminum composite foil with a thickness of 1 mm.

[0082] In step (3), each layer of mixed powder and niobium titanium aluminum composite foil has the same thickness, and a total of 11 layers are alternately stacked, including 5 layers of mixed powder and 6 layers of niobium titanium aluminum composite foil, with the top and bottom layers being niobium titanium aluminum composite foil.

[0083] After alternate lamination, the powder is wrapped with titanium foil and cold rolled at room temperature with a deformation of 25-30%, which promotes a more uniform distribution of the mixed powder.

[0084] Place it in a graphite mold uniformly sprayed with boron nitride and perform thermal diffusion composite in a vacuum sintering furnace. The specific process conditions are as follows: first, -2 MPa vacuum condition, the temperature was raised to 250°C at 7°C / min, kept at that temperature for 55 minutes, then raised to 600°C at 9°C / min, pressurized to 75MPa, kept at that temperature for 7 hours, the pressure was removed, kept at that temperature for 2 hours, and cooled to room temperature with the furnace; then -2MPa vacuum condition, heat to 1050℃ at 18℃ / min, keep warm for 35 minutes, then heat to 1230℃ at 5℃ / min, pressurize to 45MPa, keep warm and pressure for 2.5 hours, remove the pressure, keep warm for 1.5 hours, cool to room temperature with the furnace, and remove the cover.

[0085] The process conditions of laser remelting are: laser spot diameter of 3 mm, laser power of 2.5 kW, and scanning speed of 135 mm / min.

[0086] Comparative Example

[0087] A method for preparing a high-niobium porous layered titanium-aluminum alloy plate, the specific steps are as follows:

[0088] (1) Then, niobium powder, titanium dihydride powder and aluminum powder are used as raw materials to prepare niobium-titanium-aluminum alloy, and high-temperature rolling is performed for multiple passes to obtain niobium-titanium-aluminum composite foil;

[0089] (2) Finally, the niobium-titanium-aluminum composite foil and aluminum powder are alternately stacked, cold-rolled at room temperature, thermally diffused and composited, and laser remelted to obtain the high-niobium porous layered titanium-aluminum alloy sheet.

[0090] Wherein, in step (1), the niobium-titanium-aluminum alloy is prepared by the following method: firstly, niobium powder, titanium dihydride powder and aluminum powder are ball-milled and mixed in a mass ratio of 1:1.5:6, pressed into a green body under a pressure of 1 GPa, sintered, and cooled to room temperature in a furnace; the particle size of niobium powder, titanium dihydride powder and aluminum powder is 300 mesh.

[0091] The process conditions of ball milling are: ball milling at 300 r / min for 4 hours; zirconia grinding balls with a diameter of 10 mm are used for ball milling, and the ball-to-material ratio (mass ratio of grinding balls to ball-milled materials) during ball milling is 25:1.

[0092] The sintering process conditions are as follows: first increase the temperature to 500°C at 10°C / min, keep warm for 30 minutes, then increase the temperature to 900°C at 8°C / min, keep warm for 30 minutes, then increase the temperature to 1000°C at 20°C / min, keep warm for 30 minutes, and finally increase the temperature to 1200°C at 5°C / min, pass argon to 25MPa, and keep warm and pressure for 2 hours; sintering is carried out in argon atmosphere.

[0093] The specific method of multi-pass high-temperature rolling is as follows: firstly, the niobium-titanium-aluminum alloy is heated to 450°C, kept at this temperature for 20 minutes, and then high-temperature rolled under this temperature condition to finally obtain a niobium-titanium-aluminum composite foil with a thickness of 1 mm.

[0094] In step (2), the thickness of each layer of aluminum powder and the niobium-titanium-aluminum composite foil is the same, and a total of 11 layers are alternately stacked, wherein 5 layers of aluminum powder and 6 layers of niobium-titanium-aluminum composite foil are used, and the top and bottom layers are niobium-titanium-aluminum composite foils; the particle size of the aluminum powder is 300 mesh.

[0095] After alternate lamination, the mixed powder is wrapped with titanium foil and cold rolled at room temperature with a deformation of 25%, which promotes a more uniform distribution of the mixed powder.

[0096] Place it in a graphite mold uniformly sprayed with boron nitride and perform thermal diffusion composite in a vacuum sintering furnace. The specific process conditions are as follows: first, -2 MPa vacuum condition, the temperature was raised to 200°C at 5°C / min, kept at that temperature for 50 minutes, then raised to 550°C at 8°C / min, pressurized to 70MPa, kept at that temperature for 7 hours, the pressure was removed, kept at that temperature for 1 hour, and cooled to room temperature with the furnace; then -2 MPa vacuum condition, heat to 1000℃ at 15℃ / min, keep warm for 30 minutes, then heat to 1200℃ at 4℃ / min, pressurize to 40MPa, keep warm for 2 hours, remove the pressure, keep warm for 1 hour, cool to room temperature with the furnace, and remove the cover.

[0097] The process conditions of laser remelting are: laser spot diameter of 2 mm, laser power of 2 kW, and scanning speed of 130 mm / min.

[0098] Test example

[0099] The mechanical properties of the plates obtained in Examples 1 to 3 and the comparative example were examined with reference to GB / T 228-2002 “Methods for tensile testing of metallic materials”.

[0100] Low temperature resistance: Place the plate in a liquid nitrogen -196℃ environment for 10 days, take it out and return it to room temperature, and then test the mechanical properties again.

[0101] High temperature resistance: Place the plate in a 200°C environment for 10 days, take it out and return it to room temperature, and then test the mechanical properties again.

[0102] The test results are shown in Table 1.

[0103] Table 1. Results of plate performance investigation

[0104]

[0105] As can be seen from Table 1, the plates obtained in Examples 1 to 3 have excellent mechanical properties, and the mechanical properties change very little after being stored at low or high temperatures, indicating that they have excellent high and low temperature resistance.

[0106] In the comparative example, the niobium-titanium-carbon composite powder was omitted, and the mechanical properties and high and low temperature resistance of the plate were significantly deteriorated, indicating that the niobium-titanium-carbon composite powder promoted the composite between the layers, thereby improving the performance of the plate.

[0107] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.

Claims

1. A method for preparing a high-niobium porous layered titanium-aluminum alloy sheet, characterized in that: The specific steps are as follows: (1) firstly preparing niobium titanium carbon composite powder using niobium powder, titanium powder and graphite powder as raw materials, and then mixing the niobium titanium carbon composite powder with aluminum powder to obtain mixed powder; (2) Then, niobium powder, titanium dihydride powder and aluminum powder are used as raw materials to prepare niobium titanium aluminum alloy, and high-temperature rolling is performed for multiple times to obtain niobium titanium aluminum composite foil; (3) Finally, the niobium-titanium-aluminum composite foil and the mixed powder are alternately stacked, cold-rolled at room temperature, thermally diffused and composited, and laser remelted to obtain the high-niobium porous layered titanium-aluminum alloy sheet; In step (2), the niobium-titanium-aluminum alloy is prepared by the following method: firstly, niobium powder, titanium dihydride powder and aluminum powder are ball-milled and mixed in a mass ratio of 1:1.5 to 2:6 to 7, pressed into a green body, sintered, and cooled to room temperature in a furnace; the particle size of niobium powder, titanium dihydride powder and aluminum powder is 300 to 400 mesh; The specific method of multi-pass high-temperature rolling is as follows: firstly, the niobium-titanium-aluminum alloy is heated to 450-550° C., kept at this temperature for 20-30 minutes, and then high-temperature rolled under this temperature condition, and finally a niobium-titanium-aluminum composite foil with a thickness of 1 mm is obtained; In step (3), the thickness of each layer of the mixed powder and the niobium-titanium-aluminum composite foil is the same, and a total of 2n+1 layers are alternately stacked, wherein the mixed powder is n layers, the niobium-titanium-aluminum composite foil is n+1 layers, the uppermost layer and the lowermost layer are niobium-titanium-aluminum composite foil, and n is a positive integer; Place it in a graphite mold uniformly sprayed with boron nitride and perform thermal diffusion composite in a vacuum sintering furnace. The specific process conditions are as follows: first, -2 MPa vacuum condition, heat up to 200-300℃ at 5-8℃ / min, keep warm for 50-60 minutes, then heat up to 550-650℃ at 8-10℃ / min, pressurize to 70-80MPa, keep warm for 7-8 hours, remove pressure, keep warm for 1-2 hours, cool to room temperature with the furnace; then heat at 10 -2 MPa vacuum condition, heat up to 1000-1100℃ at 15-20℃ / min, keep warm for 30-40 minutes, then heat up to 1200-1250℃ at 4-6℃ / min, pressurize to 40-50MPa, keep warm for 2-3 hours, remove the pressure, keep warm for 1-2 hours, cool to room temperature with the furnace, and remove the jacket; The process conditions of laser remelting are: laser spot diameter is 2-3 mm, laser power is 2-3 kW, and scanning speed is 130-140 mm / min.

2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of niobium powder, titanium powder and graphite powder is 1:1.2-1.5:1.5-1.7; and the particle size of niobium powder, titanium powder and graphite powder is 300-400 mesh.

3. The preparation method according to claim 1, characterized in that: In step (1), the niobium-titanium-carbon composite powder is prepared by the following method: firstly, niobium powder and titanium powder are mixed by preliminary ball milling to obtain a niobium-titanium premix, and then the niobium-titanium premix is ​​further mixed by ball milling with graphite powder to obtain the niobium-titanium-carbon composite powder; the ball milling operation is carried out under an argon atmosphere; The mass ratio of niobium-titanium-carbon composite powder to aluminum powder is 7-9:

100.

4. A high-niobium porous layered titanium-aluminum alloy sheet, characterized in that: The invention is obtained by the preparation method according to any one of claims 1 to 3.

5. Application of the high niobium porous layered titanium aluminum alloy sheet material as claimed in claim 4 in aerospace material processing.

Citation Information

Patent Citations

  • A method for preparing high-niobium porous layered titanium-aluminum alloy plates

    CN110170527B

  • Niobium titanium carbon composite aluminum alloy modifier and preparation method thereof

    CN106244838A

  • Layered high niobium-titanium-aluminum alloy composite plate and preparation method thereof

    CN107900352A

  • Preparation method of high-niobium porous layered titanium-aluminum alloy sheet material

    CN110170527A